Maternal and child health book training on improving cadre skills in early detection of pregnancy risks - Asri Noviyanti; Jasmi Jasmi; Wita Asmalinda (Alma Ata University Press, 2022)
Background: Maternal and child health book (MCH) is one of the media for recording and reporting health that contains information on maternal health (pregnancy, childbirth and postpartum) and child health (monitoring growth and development, background and child health records) as well as various information on how to maintain and care for the health of mothers and children. And health cadres are one of the health service providers who have an important role in maternal and child health services. Cadres have a role in promoting and monitoring the health of pregnant women to carry out pregnancy checks in health facilities. Especially during the COVID-19 pandemic, it is necessary to be physically, mentally and socially prepared for pregnant women during pregnancy and childbirth. So that knowledge and skills are very important to be able to provide health services, early detection of pregnancy risks. Objectives: of this study was to determine the effect of MCH book training on skills in early detection of pregnancy risk. Methods: method is a quasi-experimental observational study with a two group pretest post test only design method with a total sample of 60 cadres. The interventions given were MCH book training with the face-to-face method in group I and MCH book training with the face-to-face method and presenting educational videos in the intervention group II. The research was conducted in the working area of Pembina and Pakjo Public Health Centers, Palembang City. Data analysis using mc nmar test and chi square test. Results: of the study found that there were differences in the skills of cadres in conducting early detection of pregnancy risk in both intervention group I (p=0.012) and intervention group II (p=0.000) and that there was an effect of MCH book training on skills in early pregnancy detection efforts (p=0.002; OR = ,16,789). Conclusion : of this study is that the MCH book training with the face-to-face method combined with the provision of early pregnancy risk education is able to improve the skills of cadres better than presenting MCH book training with the face-to-face method.